Phylogeny of the Sepia officinalis species complex in the eastern Atlantic extends the known distribution of Sepia vermiculata across the Benguela upwelling region. Issue 3 (25th October 2017) - Healey, AJE; McKeown, NJ; Potts, WM; de Beer, CL; Sauer, W; Shaw, PW
Abstract : Accurate species identification and biogeographic characterisation are fundamental for appropriate management of expanding cephalopod fisheries. This study addresses this topic within the common cuttlefish Sepia officinalis species complex ( S. officinalis, S. hierredda and S. vermiculata ), with an emphasis on occurrence in African waters. Tissue samples from the currently presumed distributions of S. vermiculata and S. hierredda (from South Africa and Ghana/Angola, respectively) were sequenced for the cytochrome c oxidase subunit I (COI) and the cytochrome b (cytb) genes of the mitochondrial genome and then compared to existing S. officinalis sequences. Three highly divergent and reciprocally monophyletic clades, corresponding to S. officinalis, S. hierredda and S. vermiculata, were resolved, representing the first molecular confirmation of the distinct species status of S. hierredda and S. vermiculata . The sequences also revealed that, contrary to expectations based on presently published information, all samples from southern Angola were S. vermiculata . These results indicate that the range of S. vermiculata extends beyond the currently described northern limit and that S. hierredda and S. vermiculata may be indiscriminately harvested in Angolan waters. Finer-scale patterns within S. vermiculata phylogeography also indicate that the Benguela Current System and/or other environmental factors serve to isolate northern and southern stocks.